2017
DOI: 10.22158/fsns.v1n1p43
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin, Lutein, Polyphenol Contents and Antioxidant Activity of Black, Red and White Pigmented Rice Varieties

Abstract: Colour rice varieties are rich in antioxidants and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…The red and black color of the pericarp is the main characteristic that visually differentiates them from traditional white varieties, mainly due to the accumulation of phenolic compounds. In black rice, anthocyanins are found in higher Research, Society and Development, v. 9, n. 7, e901974556, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4556 quantities among samples of the colored pericarp, in total concentrations of up to 244.45 mg/100 g, as reported by Ponnappan et al (2017). Sompong et al (2011) found that the color of dark red rice is due to the anthocyanins cyanidin-3-glucoside and peonidin-3-glucoside, with concentrations ranging from 19.4 to 140, 8 mg/100 g (d.b.)…”
Section: Physicochemical Composition and Color Of Uncooked Grainssupporting
confidence: 53%
“…The red and black color of the pericarp is the main characteristic that visually differentiates them from traditional white varieties, mainly due to the accumulation of phenolic compounds. In black rice, anthocyanins are found in higher Research, Society and Development, v. 9, n. 7, e901974556, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4556 quantities among samples of the colored pericarp, in total concentrations of up to 244.45 mg/100 g, as reported by Ponnappan et al (2017). Sompong et al (2011) found that the color of dark red rice is due to the anthocyanins cyanidin-3-glucoside and peonidin-3-glucoside, with concentrations ranging from 19.4 to 140, 8 mg/100 g (d.b.)…”
Section: Physicochemical Composition and Color Of Uncooked Grainssupporting
confidence: 53%
“…Antosianin memiliki berbagai manfaat kesehatan, salah satunya yaitu sebagai antioksidan yang bermanfaat mencegah terjadinya berbagai jenis penyakit degeneratif serta penuaan dini (Phetpornpaisan et al, 2014). Total antosianin BKH dapat mencapai 179,30 mg/100 g (Nindita et al, 2018), jauh lebih tinggi dari beras ketan putih (0,32 mg/100 g) (Ponnappan et al, 2017) maupun beras ketan merah (17 mg/100 g) (Abdullah, 2017), sehingga menjadi pilihan terbaik dalam pengolahan pangan fungsional berbasis ketan.…”
Section: Pendahuluanunclassified